Postgraduate studies in education in Ecuador - Eduardo Fabara (Universidad Politécnica Salesiana, 2012)
The following article is an investigation about the situation of postgraduate training in education in Ecuador. The study was based in the year 2010, although many aspects are analyzed taking into consideration the past of couple yearsThis research highlights the existing problems in postgraduate training programs in education, such as the lack of planning and a high need of the educational system to train specialists at this level.